International News Reporting on Nancy Pelosi’s Trip to Taiwan in 2022: A Frame Analysis - Fu, Wei-Hsin (Jurnal Komunikasi, 2025)
One of the biggest international news stories that happened in 2022 is the United States House Speaker Nancy Pelosi’s short trip to Taiwan. Under China’s coercion, Taiwan has been unable to attend many international organizations to speak out for decades. The purpose of this study is to examine the international responses via the international press’s positive/negative framing of Pelosi’s trip. This research used EBSCOhost Newspaper Source Plus to retrieve relevant news stories and used frame analysis as its research method. The timeframe started on August 1st, 2022, and ended on August 31st, 2022. A total of 164 news stories were collected from 27 news organizations across 8 countries. The results show that 121 headlines are objective reports. The number of friendly-framing news stories regarding Nancy Pelosi’s visit and Taiwan is 32. There are 11 headlines whose framing attitudes toward Taiwan and Nancy Pelosi’s visit are hostile. The friendly-framing headlines exceed the hostile ones by about three to one. The positive frames are “Democracy matters” and “China is the threat.” Negative framing includes “One China policy matters” and “The danger of starting a war.” China’s “One China principle” is presented as a universal truth, but many countries recognize only the “One China policy.” For instance, the American government does not endorse CCP’s “One China principle” and only recognizes CCP’s “One China policy.” In other words, CCP’s sovereignty claim over Taiwan is not a universal truth. The volatile issue regarding the Taiwan Strait continues.